Dual-Task Interference on Early and Late Stages of Facial Emotion Detection Is Revealed by Human Electrophysiology - Roberge, Amélie; Duncan, Justin; Fiset, Daniel; Brisson, Benoit (Frontiers in Human Neuroscience, 2019)
Rapid and accurate processing of potential social threats is paramount to social thriving, and provides a clear evolutionary advantage. Though automatic processing of facial expressions has been assumed for some time, some researchers now question the extent to which this is the case. Here, we provide electrophysiological data from a psychological refractory period dual-task paradigm in which participants had to decide whether a target face exhibited a neutral or fearful expression, as overlap with a concurrent auditory tone categorization task was experimentally manipulated. Specifically, we focused on four event-related potentials (ERP) linked to emotional face processing, covering distinct processing stages and topography: the early posterior negativity (EPN), early frontal positivity (EFP), late positive potential (LPP), and also the face-sensitive N170. As expected, there was an emotion modulation of each ERP. Most important, there was a significant attenuation of this emotion response proportional to the degree of task overlap for each component, except the N170. In fact, when central overlap was greatest, this emotion-specific amplitude was statistically null for the EFP and LPP, and only marginally different from zero for the EPN. N170 emotion modulation was, on the other hand, unaffected by central overlap. Thus, our results show that emotion-specific event-related potentials for three out of four processing stages—i.e., perceptual encoding (EPN), emotion detection (EFP), or content evaluation (LPP)—are attenuated and even eliminated by central resource scarcity. Models assuming automatic processing should be revised to account for these results.